2010
DOI: 10.1163/18759866-07904002
|View full text |Cite
|
Sign up to set email alerts
|

Zoanthids of the Cape Verde Islands and their symbionts: previously unexamined diversity in the Northeastern Atlantic

Abstract: The marine invertebrate fauna of the Cape Verde Islands contains many endemic species due to their isolated location in the eastern Atlantic, yet research has not been conducted on most taxa here. One such group are the zoanthids or mat anemones, an order of benthic cnidarians (Hexacorallia: Zoantharia) common in many marine environments. In this study, the diversity of zoanthids in the Cape Verde Islands is specifically examined for the first time. Field images and sampling are combined with molecular phyloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…For Symbiodinium ITS rDNA sequences, an alignment of ‘clade C’ ( sensu LaJeunesse ) sequences was generated from alignments of previous Symbiodinium analyses (Reimer, Takishita & Maruyama, 2006a; Reimer et al ., 2006b; Reimer, Hirose & Wirtz, 2010a) using zoanthid‐associated zooxanthellae sequences plus sequences of other clade‐C subclades from recent studies (the GenBank accession numbers are given in the resulting phylogenetic tree). The alignment consisted of primarily the second internal ribosomal space of ribosomal DNA ( ITS2 , which has been widely used in the identification of Symbiodinium types, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…For Symbiodinium ITS rDNA sequences, an alignment of ‘clade C’ ( sensu LaJeunesse ) sequences was generated from alignments of previous Symbiodinium analyses (Reimer, Takishita & Maruyama, 2006a; Reimer et al ., 2006b; Reimer, Hirose & Wirtz, 2010a) using zoanthid‐associated zooxanthellae sequences plus sequences of other clade‐C subclades from recent studies (the GenBank accession numbers are given in the resulting phylogenetic tree). The alignment consisted of primarily the second internal ribosomal space of ribosomal DNA ( ITS2 , which has been widely used in the identification of Symbiodinium types, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Pc001 does not match with any Indo-Pacific Palythoa species but fits very well with a specimen from the Cape Verde Islands named Palythoa sp. 265 [64] which is also genetically very close to P. aff. clavata [62].…”
Section: Discussionmentioning
confidence: 81%
“…265 in our concatenated analysis since ITS-rRNA sequences are not available in public databases. Nevertheless, Reimer et al [64] provided its COI sequence, the phylogenetic analysis of which confirmed a close relationship between Palythoa sp. 265 from the Cape Verde Islands and Palythoa sp.…”
Section: Discussionmentioning
confidence: 97%
“…In describing Thoracactis topsenti , Gravier (1918) incorrectly identified it as an actinian (anemone) based on the lack of zooxanthellae, channels, gaps, or cell islets. Although currently placed in the family Epizoanthidae, based on the current understanding of the type species, this genus is referable to the family Parazoanthidae, although an examination of the type material will be necessary to confirm this (see Reimer et al 2010a: 158).…”
Section: Systematicsmentioning
confidence: 99%
“…Described species currently referable to the genus Terrazoanthus are mainly from the East Pacific, with Terrazoanthus minutus from the Caribbean, and it is likely that several more undescribed species exist in the Atlantic (see Reimer et al 2010a, 2012a) and in the Central Indo-Pacific region (Reimer et al 2014b). …”
Section: Systematicsmentioning
confidence: 99%